PENGARUH LOCUS OF CONTROL DAN PENGALAMAN PRAKTIK KERJA LAPANGAN TERHADAP KESIAPAN KERJA SISWA SMK YPM 8 SIDOARJO - Hidayatulloh, M Kris Yuan; Aftoni, Aftoni; Hilmi, Mohamad Alfin (JoEMS (Journal of Education and Management Studies), 2021)
This study aims to analyze: (1) the effect of locus of control on the work readiness of mechanical engineering students; (2) the effect of internship experience on the work readiness of mechanical engineering students; and (3) the simultaneous influence of locus of control and internship experience on the work readiness of mechanical engineering students. This study uses an ex post facto method through a quantitative data approach using a questionnaire instrument distributed to students at SMK YPM 8 Sidoarjo. Data obtained from 60 students as the selected sample to be analyzed using regression. The results of this study found that: (1) there is a positive effect between locus of control on students' work readiness in mechanical engineering competence; (2) there is a positive effect between internship experience on students' work readiness in mechanical engineering competence; and (3) there is a positive effect between locus of control and internship experience simultaneously on students' work readiness in the mechanical engineering competence.